An evaluation of combat application tourniquets on training military personnel: changes in application times and success rates in three successive phases. Issue 4 (11th November 2014) - Unlu, Aytekin; Kaya, E; Guvenc, I; Kaymak, S; Cetinkaya, R A; Lapsekili, E O; Ozer, M T; Guler, A; Yildiz, R; Petrone, P; Harlak, A; Kilic, S
Abstract : Introduction: Haemorrhage from the injured extremity is a significant cause of preventable death in military settings. This study evaluated the effect of training on the efficacy of the combat application tourniquet (CAT) and to define standards for military personnel. Method: Participants from a training tank battalion were randomised. Data collected included age, body mass index, mean arterial pressure, hand dominance, femoral artery diameter and skin thickness. The study involved tourniquet application times (AT) and application success rates in basic, after-training and eyes-closed phases. Doppler ultrasound was used to identify the presence or absence of popliteal, radial and ulnar artery pulses. Results: A total of 102 trainees participated. In the after-training phase, the left and right upper extremity ATs were 35±13.1 s, and 34.8±13.5 s and the right and left lower extremity ATs were 20.6±6.0 s and 20.5±5.5 s, respectively. The overall tourniquet success rates in three successive study phases were 69.6%, 82.4% and 91.2%, respectively. A negative significant relationship was found between extremity circumference and tourniquet success. Discussion: The results show that the efficacy of CAT application increases with training. Further studies are required to investigate the reasons underlying application failures. This single group prospective randomised study involves level of evidence 4.